2023
DOI: 10.1111/josh.13367
|View full text |Cite
|
Sign up to set email alerts
|

Scoping Review of Family and Community Engagement Strategies Used in School‐Based Interventions to Promote Healthy Behaviors

Shannon L. Michael,
Seraphine Pitt Barnes,
Natalie J. Wilkins

Abstract: BACKGROUNDSchool efforts to promote health among students are more successful when families and community members are involved.METHODSWe conducted a scoping review to summarize and categorize family and community engagement strategies used in US school and out‐of‐school time (OST) interventions to address physical activity (PA) and nutrition in kindergarten through 12th grade students.RESULTSThe National Network of Partnership Schools' Six Keys to Success framework was useful in organizing the types of family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“… 24 Another manuscript in this special issue offers a robust description of parent/community engagement strategies. 88 CPSTF recommends park infrastructure improvements with additional activities, like structured programming for increasing PA. 89 CPSTF finds the economic benefits exceed the cost for park infrastructure interventions to increase physical activity and use. 90 Schools could partner with parks and recreation departments to provide transportation to afterschool PA programming in community-settings, which may increase MVPA more than school-based aftercare, 35 and confer cardiovascular benefits.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Another manuscript in this special issue offers a robust description of parent/community engagement strategies. 88 CPSTF recommends park infrastructure improvements with additional activities, like structured programming for increasing PA. 89 CPSTF finds the economic benefits exceed the cost for park infrastructure interventions to increase physical activity and use. 90 Schools could partner with parks and recreation departments to provide transportation to afterschool PA programming in community-settings, which may increase MVPA more than school-based aftercare, 35 and confer cardiovascular benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Many interventions that reported positive results for at least 1 PA or nutrition outcome provided implementation-focused professional development or technical assistance and/or engaged family or community members frequently as part of a coordinated approach. 16 18 , 22 , 32 Family and community engagement strategies to support and promote PA and nutrition in school and OST settings included communicating with families and community members; providing classes and support for families; offering volunteer opportunities for family and community members; involving families and community members in decision making; reinforcing health knowledge and practices in the home and community; and promoting collaborations among school and community to support students and their families. 32 …”
Section: Evidence-based Strategiesmentioning
confidence: 99%
“… 16 18 , 22 , 32 Family and community engagement strategies to support and promote PA and nutrition in school and OST settings included communicating with families and community members; providing classes and support for families; offering volunteer opportunities for family and community members; involving families and community members in decision making; reinforcing health knowledge and practices in the home and community; and promoting collaborations among school and community to support students and their families. 32 …”
Section: Evidence-based Strategiesmentioning
confidence: 99%
“…), and protect against nutrition-related chronic diseases (type 2 diabetes, hypertension, cardiovascular diseases, some types of cancer, etc.) that may occur in adulthood (Michael et al, 2023;Weihrauch-Blüher & Wiegand, 2018). The World Health Organization (WHO) Commission to Ending Childhood Obesity has reported that "healthy food consumption," "weight management," "increasing physical activity," "a healthy," "nutritious and active school environment," and "healthy nutrition and physical activity at an early age" are key components and targets in the prevention of childhood obesity (Ongan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%